Reverse Transcriptase Mechanism of Somatic Hypermutation: 60 Years of Clonal Selection Theory - Steele, Edward J. (Frontiers in Immunology, 2017)
The evidence for the reverse transcriptase mechanism of somatic hypermutation is substantial. In this 60th anniversary year of the publication of Sir MacFarlane Burnet's Clonal Selection Theory the evidence is briefly reviewed and updated.